2018
DOI: 10.3126/ijosh.v8i1.22922
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work-related musculoskeletal disorders in agricultural farmers of Bhaktapur District, Nepal

Abstract: Background: Work-related musculoskeletal disorders are present in a range of occupations. This is confirmed from a number of studies done around the world. However, few attempts have been done to document the presence of musculoskeletal disorders in occupational diseases in Nepal and there are hardly any studies done to see musculoskeletal disorders in farmers of Nepal. Nepal is an agricultural country and traditional practices in farming are adopted demanding a lot on the manual work. Objectives:  Aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
2
11
3
Order By: Relevance
“…This result is similar to those of several studies reporting similar shoulder pain prevalences, such as in the general population in the Netherlands (20.9%), the general population in Sweden (19.88%) [46] and dentists in Greece (19.77%) [39]. However, our results differ from those examining different populations, which reported either higher or lower prevalence rates compared to our study, such as school teachers in Saudi Arabia (59.26%) [51], nursing assistants in Norway (47.1%) [36], the working population in New Zealand (42%) [35], occupational drivers in Nigeria (30.82%) [34], agricultural farmers in Nepal (10.57%) [40], the general population in the United Kingdom (7.48%) [52] and construction workers in Saudi Arabia (4.24%) [43].…”
Section: Musculoskeletal Pain Of the Upper Limbcontrasting
confidence: 99%
See 4 more Smart Citations
“…This result is similar to those of several studies reporting similar shoulder pain prevalences, such as in the general population in the Netherlands (20.9%), the general population in Sweden (19.88%) [46] and dentists in Greece (19.77%) [39]. However, our results differ from those examining different populations, which reported either higher or lower prevalence rates compared to our study, such as school teachers in Saudi Arabia (59.26%) [51], nursing assistants in Norway (47.1%) [36], the working population in New Zealand (42%) [35], occupational drivers in Nigeria (30.82%) [34], agricultural farmers in Nepal (10.57%) [40], the general population in the United Kingdom (7.48%) [52] and construction workers in Saudi Arabia (4.24%) [43].…”
Section: Musculoskeletal Pain Of the Upper Limbcontrasting
confidence: 99%
“…In our study, the most common musculoskeletal pain of the spine among pilgrims was low back pain (28.40%). This result is similar to those of several studies that reported similar low back pain prevalences, such as among agricultural farmers in Nepal (36.18%) [40], dentists in Iran (33%) [38], the general population in the Netherlands (26.9%) [42], construction workers in Saudi Arabia (24.24%) [43] and the general population in Sweden (22.97%) [46]. However, the prevalence of low back pain in our study was slightly lower than that reported in other studies, which reported higher rates of low back pain in school teachers in Saudi Arabia (66.87%) [51], occupational drivers in Nigeria (64.78%) [34], physiotherapists in India (61.50%) [37], nursing assistants in Norway (54.9%) [36], the working population in New Zealand (54%) [35] and dentists in Greece (46.05%) [39].…”
Section: Musculoskeletal Pain Of the Spinesupporting
confidence: 92%
See 3 more Smart Citations